Panel Discussion: Bodies, Transnationalism and Affect in Recent Hispanic Poetry - Kathleen Antonioli (Studies in 20th & 21st Century Literature, 2021)
Recording of panel Discussion: Bodies, Transnationalism and Affect in Recent Hispanic Poetry
Keywords: translation; Spain; Latin America; urban; city; bodies; transnationalism; affect